When Should ED Physicians Use an HIE? Predicting Presence of Patient Data in an HIE. Issue 7 (July 2016) - Carr, Christine Marie; Saef, Steven Howard; Zhang, Jingwen; Su, Zemin; Melvin, Cathy L.; Obeid, Jihad S.; Zhao, Wenle; Arnaud, J. Christophe; Marsden, Justin; Sendor, Adam B.; Lenert, Leslie; Moran, William P.; et al.
Abstract : Objectives: Health information exchanges (HIEs) make possible the construction of databases to characterize patients as multisystem users (MSUs), those visiting emergency departments (EDs) of more than one hospital system within a region during a 1-year period. HIE data can inform an algorithm highlighting patients for whom information is more likely to be present in the HIE, leading to a higher yield HIE experience for ED clinicians and incentivizing their adoption of HIE. Our objective was to describe patient characteristics that determine which ED patients are likely to be MSUs and therefore have information in an HIE, thereby improving the efficacy of HIE use and increasing ED clinician perception of HIE benefit. Methods: Data were extracted from a regional HIE involving four hospital systems (11 EDs) in the Charleston, South Carolina area. We used univariate and multivariable regression analyses to develop a predictive model for MSU status. Results: Factors associated with MSUs included younger age groups, dual-payer insurance status, living in counties that are more rural, and one of at least six specific diagnoses: mental disorders; symptoms, signs, and ill-defined conditions; complications of pregnancy, childbirth, and puerperium; diseases of the musculoskeletal system; injury and poisoning; and diseases of the blood and blood-forming organs. For patients with multiple ED visits during 1 year, 43.8% of MSUs had ≥4 visits, compared with 18.0% of non-MSUs ( P < 0.0001). Conclusions: This predictive model accurately identified patients cared for at multiple hospital systems and can be used to increase the likelihood that time spent logging on to the HIE will be a value-added effort for emergency physicians. Abstract : Although health information exchange (HIE) is intuitively priceless as a health-improvement tool and cost-savings device, it is a relatively new and underused technology. Because of delays in physician adoption, concerns about its economic impact, and lack of stable funding, the extent to which HIE can affect American health care has yet to be appreciated and its sustainability is in question. To address these concerns the authors used descriptive data from an HIE to construct an algorithm that identified all of the patients who visited emergency departments belonging to multiple disparate hospital systems within a region during a 1-year period. This model supports the belief that focused use of HIE offers a promising approach to defragmenting American health care.